The Application of an Adaptive Reused and Ecological Architecture Architecture in the Eco-Canteen Design SMAN 1 Padalarang - Dira Nur Azizah; Tika Novis Putri*; Nova Puspa Dewi (Rumoh Journal of Architecture, 2024)
Providing a healthy and sustainable school canteen is one of the important efforts in supporting the healthy school movement, which is in line with the mission of SMAN 1 Padalarang. This design aims to apply the concepts of adaptive reuse and ecology in designing an environmentally friendly canteen. This design focuses on reusing existing and unused buildings, namely the prayer room at SMAN 1 Padalarang, to reduce environmental impacts and minimize the use of new resources. The methods used include observation, literature study, analysis of existing building conditions, and involving the school community in the design process. The process of adapting the old prayer room design into an environmentally friendly canteen involved structural evaluation, previous architectural design and assistance for canteen renovation. The design results apply the principles of ecological architecture by using environmentally friendly materials, optimizing natural light, energy efficiency and considering user comfort. Apart from that, students benefit from education about the environment, nutritious food, as well as education about murals as a medium. This design not only produces a functional and attractive space, but also serves as a concrete example of efforts to create a healthy and sustainable learning environment. accompanied by canteen management that pays attention to environmental sustainability and nutritious food for students.